The Representation of African Traditional Women in African Literature: A Feminist Study of Buchi Emecheta’S The Joys of Motherhood - Montle, Malesela Edward; Mogoboya, Mphoto Johannes (Language Circle: Journal of Language and Literature, 2022)
African women writers had not been allowed a stage to air their views about the traditional African set-up. However, with feminist winds of change sweeping from Europe to Africa in the 18th century, the social climate in most parts of the globe began to change. Minority groups challenged the Western canon and protested against their status as the second-class citizens. The groups included Afro-Americans, formerly colonized black people, women, gays, lesbians, etc. This paper focuses on one such group: black women. Being marginalised as both black and female, the African women writers started to interrogate not only the mainstream society, but also challenges faced by women in traditional African societies. The paper adopts feminism as a theory through which issues impacting African women’s lives in their respective traditional set-ups are crystallised. Feminism has various branches, of which, black womanism is one of them. As such, this paper adopts Alice Walker’s black feminism to unearth the emotions and perceptions about their daily challenges.